IMPLEMENTATION OF CORPORATE SOCIAL RESPONSIBILITY (CSR) THROUGH WAQF RELATED TO LAW NUMBER 41 YEAR 2004 ON WAQF - Helza Nova Lita (Tazkia Islamic Finance and Business Review, 2015)
Objective - Corporate Social Responsibility (CSR) is expected to continue to exist as an integral part of the management of a company. The existence of Law No. 41 Year 2004 on Waqf may be an appropriate alternative for the company to develop the concept of CSR through waqf management. Waqf is basically a form of philanthropy that is derived from Islamic law. It has its own characteristics that differentiate from other philanthropies. Characteristics of waqf  can provide a guarantee of legal protection for waqf objects that can be used to develop sustainable good deeds programs, instead of a normal charity program. The research discussess how the implementation of the concept of Corporate Social Responsibility through Waqf based on Law Number. 41 of 2004, and how the legal position of the company in the management of waqf.Methods – Analytical qualitative method on the legal aspect of waqf and theories of Islamic economics.Results - CSR within an Islamic framework includes a series of business activities in its various forms. The forms of CSR activities can be synergized through a planned management pattern, with separate funding sources.  Conclusions – The allocation of CSR through Waqf should be in accordance with the characteristics and conditions of the receiving society. Moreover, the role of  company in CSR management through waqf is either being a Wakif, Nazhir or partner of waqf institutions to improve productivity of waqf assets. Keywords : CSR, Waqf, Law